Oxygen Hyperbaric Therapy in Patients with Radiation Proctitis - Suyanto Sidik; Daldiyono H; Rianto Setiabudy; Soehartati Gondowiardjo; Vera Yuwono (The Indonesian Society for Digestive Endoscopy, 2007)
Background: Cervical cancer is the most common female malignancy in developing countries, including Indonesia. It usually occurs at the age of 20 years, reaches the peak incidence at the age of 35-55 years, and afterwards, the incidence declines. Radiotherapy is the most important treatment method in cervical cancer, especially for local advanced stage or stage IIb-IVa. It is also effective for the early stage. Oxygen hyperbaric therapy (OHBT) is defined as 100% oxygen (O2) administration of 2-3 ATA (Absolute Atmospheres) pressures in a high-pressure room. OHBT accelerates wound healing by improving oxygen perfusion around the wound and by increasing angiogenesis through Nitric Oxide Synthetase (NOS). Methods: The study was conducted at Cipto Mangunkusumo hospital, while OHBT was provided at Dr. Mintoharjo Navy Hospital. Block randomization was performed, Resulting 32 patients in OHBT group and 33 patients in control group; both groups were at normal distribution. The prevalence of radiation proctitis in OHBT and control group was determined using chi-square test. Results: By comparing the prevalence of radiation proctitis between OHBT and the control group, show that OHBT could decrease proctitis prevalence by p = 0.03. Conclusions: This study indicates that OHBT may reduce the prevalence of radiation proctitis. The OHBT is save and secure to the patients. Keywords: OHBT, cervical cancer, radiotherapy, radiation proctitis